The genome sequence of the biocontrol fungus Metarhizium anisopliae and comparative genomics of Metarhizium species. - Pattemore, J.; Hane, James; Williams, Angela; Wilson, B.; Stodart, B.; Ash, G. (Biomed Central Ltd, 2014)
Background: Metarhizium anisopliae is an important fungal biocontrol agent of insect pests of agricultural crops. Genomics can aid the successful commercialization of biopesticides by identification of key genes differentiating closely related species, selection of virulent microbial isolates which are amenable to industrial scale production and formulation and through the reduction of phenotypic variability. The genome of Metarhizium isolate ARSEF23 was recently published as a model for M. anisopliae, however phylogenetic analysis has since re-classified this isolate as M. robertsii. We present a new annotated genome sequence of M. anisopliae (isolate Ma69) and whole genome comparison to M. robertsii (ARSEF23) and M. acridum (CQMa 102).Results: Whole genome analysis of M. anisopliae indicates significant macrosynteny with M. robertsii but with some large genomic inversions. In comparison to M. acridum, the genome of M. anisopliae shares lower sequence homology. While alignments overall are co-linear, the genome of M. acridum is not contiguous enough to conclusively observe macrosynteny. Mating type gene analysis revealed both MAT1-1 and MAT1-2 genes present in M. anisopliae suggesting putative homothallism, despite having no known teleomorph, in contrast with the putatively heterothallic M. acridum isolate CQMa 102 (MAT1-2) and M. robertsii isolate ARSEF23 (altered MAT1-1). Repetitive DNA and RIP analysis revealed M. acridum to have twice the repetitive content of the other two species and M. anisopliae to be five times more RIP affected than M. robertsii. We also present an initial bioinformatic survey of candidate pathogenicity genes in M. anisopliae.Conclusions: The annotated genome of M. anisopliae is an important resource for the identification of virulence genes specific to M. anisopliae and development of species- and strain- specific assays. New insight into the possibility of homothallism and RIP affectedness has important implications for the development of M. anisopliae as a biopesticide as it may indicate the potential for greater inherent diversity in this species than the other species. This could present opportunities to select isolates with unique combinations of pathogenicity factors, or it may point to instability in the species, a negative attribute in a biopesticide.